Ethnomedicinal Plants for Cardiovascular Diseases Management in Manikganj District (Bangladesh Journal of Plant Taxonomy, 2024)
The present research deals with the identification of ethnomedicinal plants used by the local people for curing cardiovascular diseases in Manikganj district, Bangladesh. The present study aimed to record and validate the ethnomedicinal knowledge used by the local people for cardiovascular disease (CVD) management in Manikganj district, Bangladesh using recent ethnobotanical survey methods. The record of 131 ethnomedicinal plant species with diverse use patterns reflected the traditional knowledge richness in the study area. Among the ethnomedicinal plants, 10 plant species, including Phyllanthus emblica L., Allium sativum L., Terminalia arjuna (Roxb. Ex DC.) Wight & Arn, Achyranthes aspera L., Terminalia chebula Retz., Allium cepa L., Adhatoda zeylanica Nees, Cinnamomum tamala Nees & Eberm, Cajanus cajan (L.) Millsp, and Ipomea aquatica Forssk, were cited most frequently by the local people. Among the disease categories, the highest Fic (factor of informant consensus) value was obtained in cardiac complaints, followed by blood purifiers, chest pain, high blood pressure, and antioxidants. In this research, 131 plant species were recorded, and 45 plants obtained the highest Fl (fidelity level) value of 100%. The members of the most common medicinal plants were from the families of Fabaceae, Amaranthaceae, Asteraceae, Cucurbitaceae, and Apocynaceae. This result provides baseline data to link the local population, including traditional health professionals and scientific communities, which could be significant in drug discovery and is very important for the sustainable development program and conservation management in Bangladesh.Bangladesh J. Plant Taxon. 31(1): 101-121, 2024 (June)